First report of Aspergillus allahabadii Mehrotra and Agnihotri in vegetable fields in Northern Benin (West-Africa) - Affokpon, A.; Coyne, Danny L.; Tossou, C.; Coosemans, J. (2010)
Aspergillus allahabadii, previously reported only from soils in India and El Salvador, was isolated from root-knot nematode egg masses (Meloidogyne spp.) in vegetable fields in Benin. Three populations were recovered from separate fields in the Guinea savannah region from tomato and/or cabbage. The populations were morphologically identified to genus level under the microscope and to species level from molecular sequences based on ITS 1 and ITS 2 regions using purified fungi. All populations were able to produce spores on potato dextrose agar following incubation at 25 °C as well as room temperature (24 ± 2 °C), producing as many as 7.9 x 108 and 3.0 x 108 spores per plate after 10 days, respectively. Pre-planting inoculation of the populations onto tomato (cv. Tounvi) seedlings in 1-L pots increased tomato shoot and root fresh weights by up to 13 and 24 %, respectively, compared to untreated controls after five weeks. The three populations all successfully established and remained in the rhizosphere of tomato plants until termination of the experiment at seven weeks after inoculation. Given that the populations were all isolated from nematode egg masses, the current study can be considered as the starting point for further research on their possible use for biological control.